Integrating neuroscience and oncology: neuroimmune crosstalk in the initiation and progression of digestive system tumors - Haonan Sun; Tao Wang; Xiangyan Jiang; Mingdou Li; Xiaoe He; Yong Ma; Xiangkai Li; Weilin Jin; Zuoyi Jiao (Molecular Cancer)
Abstract Recent global data show that cancers of the digestive system are responsible for approximately one-third of all cancer-related deaths worldwide, underscoring the urgent need for innovative therapeutic strategies. In this context, emerging findings from neuroscience may unveil new avenues for tackling this pressing clinical problem. Over the past few years, rapid progress in cancer neuroscience has increasingly underscored the contribution of the nervous system to the development and progression of digestive tract tumors. Research has shown that the specialized neural network of the gastrointestinal tract establishes a framework for reciprocal interactions with digestive tract tumors. On this anatomical foundation, our review delves into the functional significance of these interactions, emphasizing the bidirectional regulatory pathways between the nervous system and tumor cells during disease progression and highlighting their intricate crosstalk with the immune microenvironment. In particular, it maps the molecular pathways by which both the central and peripheral nervous systems (PNS) modulate tumor initiation and progression. Moreover, it explains how neurotransmitters and neuroendocrine mediators drive tumor expansion through the activation of canonical oncogenic signaling cascades and the remodeling of the immunosuppressive microenvironment. This review seeks to elucidate the molecular underpinnings of neuro-immune-tumor crosstalk and to synthesize the latest neural-targeted therapeutic approaches. It also examines the principal obstacles that are impeding the clinical implementation of these interventions. By presenting an integrated overview, this work serves as a robust resource to inform future studies on neurobiological mechanisms and the development of novel therapies for gastrointestinal malignancies.